Detection of the Allelic Repeat in the TERT Gene At the Rs2736100 Locus in Diabetic Patients Using PCR and Sequencing Technology - Kamil, Noor Rassam (American Journal of Biology and Natural Sciences, 2026)
Type 2 diabetes mellitus (T2DM) is a multifactorial condition that impacts multiple organs and might modify telomerase activity, expressed by the hTERT gene, potentially influencing telomere length. The study aimed to investigate of the allelic repeat in the TERT gene at the rs2736100 locus in diabetic patients using PCR and sequencing technology. A total of 4030 subjects (60 Diabetic patients; 10 age-matched healthy controls) were included. Peripheral blood was obtained for molecular analysis. Rs2736100 genotyping was conducted by PCR combined with Sanger sequencing, and genotyped for telomerase reverse transcriptase (TERT) rs2736100 using TaqMan custom SNP genotyping assay. The frequency of the wild-type genotype (GG) which was the references allele was more frequently in control groups at 100% than in patient group 53.33%. The mutant homozygous genotype (AA) appeared only in diabetic patients (1.34%), also the heterozygous genotype (AG) was observed in 33.33% of diabetic patients and not found in healthy individuals.The odds ratio (OR) for the AG and AA genotype was (19.727, 8.454) (95% CI: 1.063 - 365.978, 0.419 - 170.311; p = 0.01). At the allelic level, the G allele was highly frequent in the control group (100%) compared to the diabetic group (70%). Conversely, the A allele was observed in diabetic group only (30%). A single sharp G signal at the polymorphic location confirmed a homozygous wild genotype (GG) in numerous samples. Some chromatograms showed overlapping G and T nucleotide peaks at the same location, indicating a heterozygous genotype. The study investigates three genotypes (homozygous GG, heterozygous GT and mutant homozygous TT). The GT genotype was more frequent with 46% (12/26) followed by GG with 42%(11/26) while the TT was the least frequent with 11%(3/26). Based on allele frequency, G allele (normal) was more frequent with 65% (34/52) than T(mutant) with 35%(18/52). This particular variant, rs2736100, is an intron variant, meaning it is located outside of the gene's coding area. The polymorphism of telomerase reverse transcriptase(TERT) rs 2736100 variants are associated with the susceptibility of type 2 diabetes mellitus.